Strontium vanadate-supported graphitic carbon nitride nanocomposite for simultaneous voltammetric determination of acetaminophen and levofloxacin in complex biological samples. Issue 10 (14th September 2022) - Nataraj, Nandini; Chen, Shen-Ming; Krishnan, Siva Kumar
Abstract : Simultaneous electrochemical determination of antibiotic drugs such as acetaminophen and levofloxacin using SrV NPs decorated graphitic carbon nitride (SrV/GCN) nanocomposite. Abstract : In this study, we report a simple approach to preparing platelet-like strontium vanadate (SrV) supported on a graphitic carbon nitride (SrV/GCN) nanocomposite using a two-step synthesis process. An SrV/GCN nanocomposite modified glassy carbon electrode (GCE) was explored for the highly selective simultaneous electrochemical detection of the antibiotic drugs acetaminophen (ACAMP) and levofloxacin (LEV). The structure, morphology, and crystalline features of the SrV/GCN nanocomposite were characterized using different microscopy and spectroscopic techniques. The incorporation of SrV nanostructures onto GCN can remarkably improve the active surface area, electrical conductivity, and electrochemical performance. As a result, the constructed SrV/GCN/GCE sensor exhibits a remarkably high sensitivity of 15.79 and 14.27 μA μM −1 cm −2, a wide linear range of 0.019–1100 μM, and a low detection limit (LOD) of 0.026 and 0.028 μM for ACAMP and LEV, respectively. Moreover, the sensor showed exceptional selectivity and operational stability for the simultaneous detection of ACAMP and LEV without any interference effects. Finally, the practical use of the proposed sensor was validated in spiked real samples, such as human blood serum, human urine, commercial antibiotic tablets, and river water samples, offering promising opportunities for practical clinical analysis.